Randomised field trial to evaluate serological response after foot-and-mouth disease vaccination in Turkey - Knight-Jones, Theodore J.D.; Bulut, A.N.; Gubbins, S.; Stark, K.D.C.; Pfeiffer, Dirk U.; Sumption, Keith J.; Paton, D.J. (Elsevier, 2015)
Despite years of biannual mass vaccination of cattle, foot-and-mouth disease (FMD) remains uncontrolled in Anatolian Turkey. To evaluate protection after mass vaccination we measured post-vaccination antibodies in a cohort of cattle (serotypes O, A and Asia-1). To obtain results reflecting typical field protection, participants were randomly sampled from across Central and Western Turkey after routine vaccination. Giving two-doses one month apart is recommended when cattle are first vaccinated against FMD. However, due to cost and logistics, this is not routinely performed in Turkey, and elsewhere. Nested within the cohort, we conducted a randomised trial comparing post-vaccination antibodies after a single-dose versus a two-dose primary vaccination course. Four to five months after vaccination, only a third of single-vaccinated cattle had antibody levels above a threshold associated with protection. A third never reached this threshold, even at peak response one month after vaccination. It was not until animals had received three vaccine doses in their lifetime, vaccinating every six months, that most (64% to 86% depending on serotype) maintained antibody levels above this threshold. By this time cattle would be >20 months old with almost half the population below this age. Consequently, many vaccinated animals will be unprotected for much of the year. Compared to a single-dose, a primary vaccination course of two-doses greatly improved the level and duration of immunity. We concluded that the FMD vaccination programme in Anatolian Turkey did not produce the high levels of immunity required. Higher potency vaccines are now used throughout Turkey, with a two-dose primary course in certain areas. Monitoring post-vaccination serology is an important component of evaluation for FMD vaccination programmes. However, consideration must be given to which antigens are present in the test, the vaccine and the field virus. Differences between these antigens affect the relationship between antibody titre and protection.